Energy Efficiency Comparison of MIMO-Based and Multihop Sensor Networks. (24th December 2007) - Bravos, George; Kanatas, Athanasios G.
Abstract : Wireless sensor networks (WSNs) demand the implementation of energy-aware techniques and low-complexity protocols in all layers. Recently, a MIMO-based structure has been proposed to offer enhanced energy savings in WSNs. In this paper, we examine and compare MIMO-based WSN with a multihop transmission in terms of energy efficiency. The results depend on the network density, the channel conditions, and the distance to the destination node. We reach analytical expressions to calculate threshold values of these parameters, which determine the areas where the MIMO-based structure outperforms multihop transmission. Moreover, we present a detailed analysis of the dissipated power during a sensor node_s operation, to prove that as microelectronics develops, the MIMO-based architecture will outperform the equivalent multihop structure for most of the cases examined. Finally, we implement a simple cooperative node selection algorithm to achieve higher energy gains in the MIMO approach, and we examine how this algorithm affects the calculated thresholds.